Corrigendum: A study on the effects of hybrid (SIC- PSSA) nano sized reinforcement on mechanical and tribological behaviour of Al alloy-based metal matrix composite produced by ultrasonic assisted stir casting (2024 Mater. Res. Express 11 075010) - Nagaraju Tenali; G Ganesan; P Ravindra Babu (Materials Research Express)
This study focuses on the effects of hybrid reinforcement consisting of nanosized particles of Palm Sprout Shell Ash (PSSA) and silicon carbide (SiC) on the mechanical and tribological properties of the Al-Cu-Mg alloy. Hybrid reinforced composites with different weight percentages of SiC and PSSA (0:0, 0:4, 1:3, 2:2, and 4:0 wt%) were prepared using the ultrasonic-assisted bottom-poured stir casting technique. Scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDS) were used to characterize the hybrid composite made of Al-Cu-Mg alloy. The optical and SEM microstructural analyses demonstrated an even distribution of SiC and PSSA nanosize reinforcements within the matrix. The EDS analysis revealed SiC and PSSA reinforcement particles in the composite. The mechanical properties (tensile, flexural, and impact strength) and wear properties (wear rate and coefficient of friction) of the composites and alloys were evaluated according to the ASTM standards. The hybrid reinforced composites outperformed the base alloy. Among all composites, the 2:2 wt% SIC and PSSA hybrid-reinforced composites exhibited a significant enhancement in both tensile and flexural strength, with a 22.64% and 27.64% increase in strength, respectively. However, the inclusion of these reinforcements led to a reduction in the ductility and impact strength of the Al-Cu-Mg alloy composite. The 0:4 wt% SiC- and PSSA-reinforced composites experienced the largest reductions in ductility and impact strength, with decreases of 47.67% and 4.38%, respectively. For the 2:2 wt% SiC and PSSA composites, these reductions were 23.64% and 3.19%, respectively. The SEM analysis of the fractured surfaces of the composites tested for mechanical properties revealed evidence of both ductile and brittle fracture mechanisms in the tensile, flexural, and impact tests. The wear behaviour of the prepared samples was evaluated, and all composites exhibited superior performance compared with the base alloy, demonstrating adhesive and abrasive wear mechanisms and varying friction coefficients. Among all the composites, the 2:2 wt% SiC- and PSSA-reinforced composites exhibited high wear resistance and a lower coefficient of friction than the other fabricated composites.